Maximizing .NET Performance - Wienholt, Nick (Apress, 2012)
Like other areas of nonfunctional software production, performance is often an afterthought to the construction process, and needs to be tacked onto an existing code base. With a new platform like .NET, the negative consequences of this production practice is more pronounced, as developers and architects do not have the same depth of experience that they did in the unmanaged world. In the Internet age, producing software with adequate performance characteristics is more important than ever, and in a climate of shrinking IT budgets, throwing hardware at poorly performing systems is no longer an option.